Analysis of The Influence of Management, Technical, and Digitalization Factors on Cost Performance through Green Shorebase Performance Based on Value Engineering - Shalwa An-nisa Addawiyah; Agus Suroso (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2025)
The global maritime sector contributes around 2.5% of total CO2 emissions, the majority of which originate from shipping and port operations. Shorebase is a port that plays an essential role in the oil and gas sector, but its logistical activities add significantly to overall port emissions. The implementation of green ports at shorebase is a method and resolve to emphasize the importance of a safe environment. This study analyzes the influence of management, technical, and digitalization factors on cost performance in a green shorebase project using Value Engineering (VE) and Life Cycle Cost Analysis (LCCA). Results show the technical aspect has the most significant impact at 58%, followed by management (20.6%) and digitalization (20%). Green shorebase performance contributes 97% to cost performance. VE implementation generated operational cost savings of IDR 1,135,948,542 or 7% of initial costs, exceeding efficiency benchmarks (Ekanayake et al., 2018). LCCA results indicate the project is feasible, with a Benefit Cost Ratio of 3.33, NPV of IDR 25,989,577,423, IRR of 49% (above the 20% discount factor), and a payback period of 3.93 years. These findings confirm that VE and LCCA are effective in optimizing costs and improving project feasibility. This research serves as a reference for applying green and smart port concepts in Indonesian shorebase projects.